Corporate criminal liability emergence, convergence, and risk - Ivory, Radha; Pieth, Mark (Ius gentium: Comparative Perspectives on Law and Justice, 2011)
With industrialization and globalization, corporations acquired the capacity to influence societies for better or worse. Yet, corporations are not traditional objects of criminal law. Justified by notions of personal moral guilt, criminal norms have been judged inapplicable to fictional persons who 'think' and 'act' through human beings. The expansion of new corporate criminal liability (CCL) laws since the mid-1990s challenges this assumption. This volume surveys current practice on CCL in diverse civil and common law jurisdictions, exploring the legal conditions for liability, the principles and options for sanctioning, and the procedures for investigating, charging, and trying corporate offenders. It considers whether domestic CCL laws are converging around the notion of 'due diligence' and, in any case, the implications of CCL for those charged with keeping corporations, and other legal entities, out of trouble